2013
DOI: 10.1371/journal.pone.0067723
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Properties Analysis of Botanical Insecticide Rhodojaponin III-Induced Response of the Diamondback Moth, Plutella xyllostella (L.)

Abstract: BackgroundRhodojaponin III, as a botanical insecticide, affects a wide variety of biological processes in insects, including reduction of feeding, suspension of development, and oviposition deterring of adults in a dose-dependent manner. However, the mode of these actions remains obscure.Principal FindingsIn this study, a comparative proteomic approach was adopted to examine the effect of rhodojaponin III on the Plutella xyllostella (L.). Following treating 48 hours, newly emergence moths were collected and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 53 publications
0
22
0
3
Order By: Relevance
“…Both proteomic approaches have been increasingly adopted for insect pest management research (Table ). The examples of applications include insect–plant host interactions (Dastranj, Gharechahi, & Salekdeh, ), characterizing mechanism of action of synthetic and bio‐based insecticides (Dong et al, ; Erban, Harant, Chalupnikova, Kocourek, & Stara, ; J. M. Park et al, ; Roat et al, ), assessing impact of insecticides of nontarget organisms (Vioque‐Fernández, De Almeida, & López‐Barea, ), and characterizing EPM in managing insect pests. Contemporary proteomics research has the options of adopting gel‐based or MS‐based, labeled or nonlabelled approach to answer biological questions (Figure ).…”
Section: Proteomics and Its Potential For Characterizing Microbe–hostmentioning
confidence: 99%
“…Both proteomic approaches have been increasingly adopted for insect pest management research (Table ). The examples of applications include insect–plant host interactions (Dastranj, Gharechahi, & Salekdeh, ), characterizing mechanism of action of synthetic and bio‐based insecticides (Dong et al, ; Erban, Harant, Chalupnikova, Kocourek, & Stara, ; J. M. Park et al, ; Roat et al, ), assessing impact of insecticides of nontarget organisms (Vioque‐Fernández, De Almeida, & López‐Barea, ), and characterizing EPM in managing insect pests. Contemporary proteomics research has the options of adopting gel‐based or MS‐based, labeled or nonlabelled approach to answer biological questions (Figure ).…”
Section: Proteomics and Its Potential For Characterizing Microbe–hostmentioning
confidence: 99%
“…Recent studies on insect proteomics have given insight into the molecular mechanisms of larva development, diapauses and resistance mechanisms (Colinet et al 2012;Konus et al 2013;Li et al 2014a;Yin et al 2017;Zhang et al 2013). Differential proteomics which aimed to understand protein regulation during normal and treatment status were applied in several insecticides resistance and susceptibility response studies of P. xylostella (Dong et al 2013;Xie et al 2011;Yin et al 2017;Zhang et al 2013). These results suggested that the insecticides treatment have induced alteration in protein, which are participated in the nervous transduction and multiple metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…xylostella (Xie et al 2011) while tris lysis buffer methods were applied to extract the protein from P. xylostella adult tissues (Dong et al 2013). In addition, TCA-acetone with dithiothreitol (DTT) was used to extract the protein from P. xylostella adult (Zhang et al 2013) and larva (Yin et al 2017) tissues.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations